'Carrying the fire' : Cormac McCarthy's moral philosophy - Davies, Christopher (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2011)
In this thesis, I argue that the question of ethics, despite claims to the contrary, is a central concern in Cormac McCarthy's fiction. My principal contention, in this regard, is that an approach that is not reliant on conventional systems of meaning is needed if one is to engage effectively with the moral value of this writer's oeuvre. In devising such an approach, I draw heavily on the 'immoralist' writings of Friedrich Nietzsche. The first chapter of the study contends that good and evil, terms central to conventional morality, do not occupy easily definable positions in McCarthy's work. In the second chapter, the emphasis falls on the way in which language and myth's mediation of reality informs choice. The final chapter focuses on the post-apocalyptic setting of The Road, in which normative systems of value are completely absent. It argues that, despite this absence, McCarthy presents a compassionate ethic that is able to find purchase in the harsh world depicted in the novel. Finally, then, this study argues that McCarthy's latest novel, The Road, requires a reconsideration of the critical claim that his work is nihilistic and that it negates moral value.
Keywords: McCarthy, Cormac, 1933- -- Criticism and interpretation; American fiction -- 20th century -- Moral and ethical aspects; American fiction -- 20th century -- History and criticism